Multisystem inflammatory syndrome in children with COVID-19 in a multitransfused patient - Swarnalata Das; Manas Behera Ranjan; Palash Das (Asian Journal of Transfusion Science)
Multi-system inflammatory syndrome in children associated with COVID19 (MIS-C) is a unique clinical syndrome characterised by fever, gastrointestinal symptoms, skin and oral rash and or neurological symptoms in the presence of raised acute phase reactants and coagulopathy. Ferritin is an acute phase reactant which is used as a marker of inflammation. Diagnosis of MIS-C in the background of transfusion dependent thalassemia with iron overload needs a strong clinical suspicion. Early diagnosis and prompt treatment are necessary to ensure a rapid uneventful recovery. A three-year-old male child born to non-consanguineously related parents reported to pediatric emergency with difficulty breathing and pain abdomen for one day. The child was a diagnosed case of Beta thalassemia major since the age of one year and was on regular transfusions and was on iron chelation for past eleven months with deferrasirox. Initial clinical examination showed a sick and irritable child with tachypnea tachycardia and hypoxia. Initial investigations showed raised acute phase reactants along with severe anemia. The child was investigated for MIS-C because of unexpected rise of serum ferritin from 1980 ng/mL (October 2020) to 6686 ng/mL (in January 2021) despite being on regular chelation. Antibody titre for SARS COVID-19 was positive. The patient was treated with intravenous corticosteroids and improved with the same. The advent of COVID19 pandemic saw most children having a mild disease with no or minimal symptoms. Some kids however presented with more serious delayed symptoms of MIS-C. To diagnose same in multi transfused patients a strong clinical suspicion and just judgement based on the clinical and laboratory findings should be done. Unexplained rise in ferritin levels, typical symptoms and high probability of exposure to COVID19 helped in clinching diagnosis.